2020
DOI: 10.1007/s00428-020-02962-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center real-world comparison of the fully automated Idylla™ microsatellite instability assay with routine molecular methods and immunohistochemistry on formalin-fixed paraffin-embedded tissue of colorectal cancer

Abstract: Microsatellite instability (MSI) is present in 15–20% of primary colorectal cancers. MSI status is assessed to detect Lynch syndrome, guide adjuvant chemotherapy, determine prognosis, and use as a companion test for checkpoint blockade inhibitors. Traditionally, MSI status is determined by immunohistochemistry or molecular methods. The Idylla™ MSI Assay is a fully automated molecular method (including automated result interpretation), using seven novel MSI biomarkers (ACVR2A, BTBD7, DIDO1, MRE11, RYR3, SEC31A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
5
30
0
Order By: Relevance
“…They also demonstrated SEC31A to be a gene with no extreme specificity to harbor frameshift MSI in either CRC or EC genomes. Further, the multicenter Idylla MSI test study of CRC reported ACVR2A to be the most often mutated biomarker (94.0%) and SEC31A to be the least mutated marker (60.9%) [11], and our frequencies are in line with a sequencing study demonstrating ACVR2A mutations in 92% and SEC31A mutations in 54% of one hundred MSI CRC cases [27].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They also demonstrated SEC31A to be a gene with no extreme specificity to harbor frameshift MSI in either CRC or EC genomes. Further, the multicenter Idylla MSI test study of CRC reported ACVR2A to be the most often mutated biomarker (94.0%) and SEC31A to be the least mutated marker (60.9%) [11], and our frequencies are in line with a sequencing study demonstrating ACVR2A mutations in 92% and SEC31A mutations in 54% of one hundred MSI CRC cases [27].…”
Section: Discussionsupporting
confidence: 87%
“…In this report, one case was MSS in Idylla analysis, whereas IHC was dMMR and Promega MSI analysis was MSI and interestingly tumor mutation burden was very high, whereas three IHC dMMR cases showed MSS in DNA-based assays and low tumor mutation burden. In addition, a multi-center real-life global study including 44 clinical centers and 1301 CRC samples showed the concordance level between the Idylla test and IHC to be as high as 96.4%, with Idylla having lower failure rates [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Idylla ® MSI assay (Bioartis, NV, Mechelen, Belgium) is a fully-automated PCR-based system that comprises the analysis of seven novel monomorphic homopolymer regions ( ACVR2A , BTBD7 , DIDO1 , MRE11 , RYR3 , SEC31A , SULF2 ) in a single-use cartridge with all reagents on board ( Table 2 ) [ 74 ]. In colorectal, endometrial, and gastric cancers, the Idylla ® system provides a high concordance (>96%) and lower failure rate compared to the standard reference methods [ 75 , 76 , 77 , 78 ]. Less is known about its performance in other cancers and further studies are needed to confirm its interest in such cases [ 79 ].…”
Section: Other Msi Approaches On Tumour Tissue Samplesmentioning
confidence: 99%
“…The Idylla™ MSI Assay from Biocartis (Mechelen, Belgium) was used according to the manufacturer’s instructions to determine whether tumors were MSS or MSI ( 23 ). In 35 of the 58 cases, isolated DNA was available from CLM samples as previously described ( 7 ), while in 23 cases, FFPE tissue was used [from CLM resection sample (n = 20) or from the pCRC sample (n = 3)].…”
Section: Methodsmentioning
confidence: 99%